2010
DOI: 10.1016/j.schres.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparisons of metabolic side effects of second generation antipsychotics in the treatment of schizophrenia: A systematic review and meta-analysis

Abstract: Objective-The metabolic side effects of second-generation antipsychotics (SGA) are serious and have not been compared head to head in a meta-analysis. We conducted a meta-analysis of studies comparing the metabolic side effects of the following SGAs head-to-head: amisulpride, aripiprazole, clozapine, olanzapine, quetiapine, risperidone, sertindole, ziprasidone, zotepine.Method-We searched the register of the Cochrane schizophrenia group (last search May 2007), supplemented by MEDLINE and EMBASE (last search Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
414
5
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(440 citation statements)
references
References 32 publications
15
414
5
6
Order By: Relevance
“…A recent meta-analysis showed that all antipsychotic drugs are associated with weight gain (Bak et al, 2014). Moreover, antipsychotic medication is not only related to weight gain in schizophrenia but also in other severe mental disorders (Bak et al, 2014;Parsons et al, 2009;Rummel-Kluge et al, 2010). In the following, we will review evidence for a common pharmacological mechanism and a relation to reward anticipation.…”
Section: Role Of Medication In Weight Gainmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis showed that all antipsychotic drugs are associated with weight gain (Bak et al, 2014). Moreover, antipsychotic medication is not only related to weight gain in schizophrenia but also in other severe mental disorders (Bak et al, 2014;Parsons et al, 2009;Rummel-Kluge et al, 2010). In the following, we will review evidence for a common pharmacological mechanism and a relation to reward anticipation.…”
Section: Role Of Medication In Weight Gainmentioning
confidence: 99%
“…While the amount of weight gain resulting from different antipsychotics may vary, when looking for a common mechanism, we need to consider which specific pharmacological properties olanzapine or clozapine have that ziprasidone or aripiprazole do not (these specific properties are documented in a meta-analysis of head-to-head trials by Rummel-Kluge et al, 2010). One candidate mechanism of increased weight gain is the antihistaminergic property of both olanzapine and clozapine (Deng et al, 2010).…”
Section: Role Of Medication In Weight Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine generell anzuwendende, initiale Standardmedikation mit Antipsychotika und ihre jahrelange Fortführung in "wirksamer Dosis" ohne Empfehlungen zur längerfristigen Dosisminderung mit dem Argument der Rückfallprophyla-xe entsprechend vieler Leitlinien [124] ist bei insgesamt minimaler [125] bis mäßi-ger [126] Verbesserung der Symptomatik durch Antipsychotika kritisch zu diskutieren. Die erwünschten Wirkungen der Antipsychotika sind gegen die oft dosisabhän-gigen und teilweise schweren metabolischen Nebenwirkungen [127,128,129], die im Alter noch deutlich zunehmen [130], und angesichts des erhöhten Risikos von Diabetes [131,132] und koronaren Herzerkrankungen [133] abzuwägen. Dies gilt insbesondere für Kinder und Jugendliche, bei denen die Nebenwirkungen oftmals besonders ausgeprägt sind [134,135].…”
Section: Therapeutische Schlussfolgerungenunclassified
“…The type of anti-psychotic drug or illness itself might increase the risk of developing diabetes (Bushe and Leonard, 2004;Melkersson and Dahl, 2004;Rummel-Kluge et al, 2010) and secondary hormonal changes may influence the metabolic changes (Bushe and Leonard, 2004;Melkersson and Dahl, 2004;Rummel-Kluge et al, 2010). .…”
Section: Introductionmentioning
confidence: 99%